Pengaruh Self Assesment System, Sosialisasi Perpajakan dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Silaban, Yenniper Novelen E; Efriyenti , Dian (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The tax sector has a dominant role in the economy in Indonesia. The method applied in this research is a quantitative approach (Positivism). This research uses primary data obtained through questionnaires. This study uses the Slovin formula with a margin error rate of 10%, the population in this study was 75,569 and the sample obtained was 100 respondents. This questionnaire was distributed to respondents collected from the Batam Pratama Selatan Tax Service Office (KPP) during the period 2019 to 2023. Self Assessment The system has a significant effect on individual taxpayer compliance at KPP Pratama South Batam, so H1 accepted. Tax socialization has a significant effect on individual taxpayer compliance at KPP Pratama South Batam, so H2 is accepted. Tax sanctions have a significant effect on individual taxpayer compliance at KPP Pratama South Batam, so H3 is accepted. The Self Assessment System, Tax Socialization, Tax Sanctions simultaneously have a significant effect on individual taxpayer compliance at KPP Pratama South Batam, so H4 is accepted.